Three concepts: an academic ecologist’s view - Alexander Protasov (Geo&Bio)
Human activity not only creates new materials and technologies, changes the nature of natural geochemical processes, which can have a local impact on the biosphere and the processes in it, as V.I. Vernadsky pointed out, but also creates new types of ecosystems—urban ecosystems, where man builds completely new elements and entire systems of biotopes for the existence of their populations, agroecosystems, where through the use of agricultural technology receives the necessary products of a limited number of species of organisms. It also creates techno-ecosystems, where natural elements together with artificial, technical elements create habitats for organisms. The noospherogenesis, in fact, is the formation of a coexisting system of natural and anthropogenic ecosystems. General ecological principles, which to a greater or lesser extent are addressed in the ‘Concept of balanced (sustainable) development of agroecosystems in Ukraine for the period up to 2025,’ as well as proposals for the creation of the ‘Concept of effective and safe operation of techno-ecosystems’ are considered. It is pointed out that the concept of ‘agroecosystem’ should be considered quite broadly, since it can include not only landscapes, but also aquatic environments. Anthropodependent biotic communities include not only agricultural plants, but also a full spectrum of organisms, from bacteria to mammals. It is pointed out that there is a contradiction between the idea of preserving biodiversity in ecosystems and the high productivity of certain significantly dominant populations. It is noted that technical objects do not exist separately from the environment, but create various techno-ecosystems with natural elements, in which there is a close relationship and mutual influence of technical and biotic elements and factors. The environment is also impacted not by technical systems, but by techno-ecosystems. As one of the factors of scientific and practical support of activities in the field of agroecosystems and techno-ecosystems development management, the directions of scientific research in the concept of research development in the Academy of Sciences of Ukraine are considered. Some issues of practical use of the provisions of the EU Water Framework Directive are discussed, namely in the aspect of application to aquatic techno-ecosystems. During military operations, the destructive power of anthropogenic factors increases by many times, the importance of different factors shifts, which should be reflected in the general conceptual provisions of the complexes of interrelations between nature and human activity.